Pozycja prawna Szefa Kancelarii Prezydenta Rzeczypospolitej Polskiej - Szluz, Anna (Wydawnictwo Adam Marszałek, 2019)
The article presents the legal position of the Chief of the Chancellery of the President of Poland. The President has an influence on shaping the closest surroundings (selection of the Chief is the sovereign decision of the President). The Chief manages the work of the Presidential Chancellery, represents it and stands at its head. The strong position of the Chief should be emphasized. The purpose of this study was to investigate the legal position of Chief as defined by the Constitution and the Statute of the Presidential Chancellery.

Artykuł prezentuje pozycję prawną Szefa Kancelarii Prezydenta Rzeczypospolitej Polskiej. Prezydent ma wpływ na dobór swojego najbliższego otoczenia (dobór Szefa jest jego suwerenną decyzją). Szef kieruje pracami Kancelarii, reprezentuje ją oraz stoi na jej czele. Należy podkreślić jego silną pozycję. Celem rozważań było przedstawienie jego pozycji prawnej, która wynika z Konstytucji i Statutu Kancelarii Prezydenta.
The legal position of the Chief of the Chancellery of the President of Poland
-
Keywords: President; Chief of the Chancellery of the President; Presidential Chancellery; Prezydent; Szef Kancelarii Prezydenta; Kancelaria Prezydenta